Pengaruh Faktor Individu dan Lingkungan Fisik Terhadap Keluhan Muskuloskeletal Pada Pekerja Administrasi Perkantoran: Systematic Literature Review - Yeti Patiroh; Dinni Agustin; Nur Apriyan (JURNAL BIDANG ILMU KESEHATAN, 2026)
Musculoskeletal disorders (MSDs) are among the most common occupational health problems experienced by administrative office workers. Work activities involving prolonged static sitting, combined with non-ergonomic postures and inadequate physical work environments, have a high potential to cause musculoskeletal problems. In addition, individual factors such as age, gender, body mass index (BMI), and health history also contribute significantly to the occurrence of MSDs. This study aims to systematically review the influence of individual factors and the physical work environment on musculoskeletal complaints among administrative office workers. The method employed was a SLR using the PRISMA approach. Literature searches were conducted in Google Scholar, PubMed, Semantic Scholar, and UI ScholarHub databases for publications from 2019–2025. The inclusion criteria consisted of peer-reviewed articles focusing on office administrative workers, discussing individual factors or physical work environment related to MSDs, and published in English or Indonesian. Articles without full text, non-empirical studies, and studies involving non-office workers were excluded. The selected studies were analyzed using thematic synthesis to identify patterns and relationships between risk factors and musculoskeletal complaints. Out of 132 identified articles, 20 articles met the inclusion criteria and were selected for further analysis. The findings indicate that age over 40 years, BMI ≥ 25, non-ergonomic working postures, and inadequate work equipment are the main determinants of musculoskeletal complaints. The body parts most frequently affected were the neck, lower back, and shoulders. This review recommends the implementation of ergonomic education, the provision of appropriate work facilities, and regular health evaluations to reduce the risk of MSDs among office workers